2011
DOI: 10.1063/1.3532409
|View full text |Cite
|
Sign up to set email alerts
|

Variational second order density matrix study of $\mathrm{F_3^-}$F3−: Importance of subspace constraints for size-consistency

Abstract: Variational second order density matrix theory under '2-positivity' tends to dissociate molecules into unphysical fractionally charged products with too low energies. We aim to construct a qualitatively correct potential energy surface for F − 3 by applying subspace energy constraints on mono-and diatomic subspaces of the molecular basis space. Mono-atomic subspace constraints do not guarantee correct dissociation: the constraints are thus geometry dependent. Furthermore, the number of subspace constraints nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Additionally, the inconsistencies that arise in the dissociation limit of the maximal spin projections of degenerate spin states, such as those occurring in the dissociation limit of the oxygen and carbon dimer, can be corrected by imposing subspace energy conditions. 12,13,30 At the same time, these constraints will correct size-consistency defects and incorrect dissociation-in contrast to the molecules under consideration here, non-homonuclear molecules gener- FIG. 9.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, the inconsistencies that arise in the dissociation limit of the maximal spin projections of degenerate spin states, such as those occurring in the dissociation limit of the oxygen and carbon dimer, can be corrected by imposing subspace energy conditions. 12,13,30 At the same time, these constraints will correct size-consistency defects and incorrect dissociation-in contrast to the molecules under consideration here, non-homonuclear molecules gener- FIG. 9.…”
Section: Resultsmentioning
confidence: 99%
“…10 An approach taken by Hammond and Mazziotti avoids the problem of dealing with a non-singlet spin states by coupling them to an overall singlet state. 10 However, because of the inherent size-inconsistency of approximate N-representability constraints (and, more importantly, of approximate S-representability constraints, as we will show here) and their tendency to allow fractional charges in non-interacting systems, [11][12][13] this approach is problematic.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…It has been repeatedly demonstrated that v-2RDM methods are not size-consistent, a deficiency which manifests itself in the tendency of the methods to favour fractional charges in non-interacting subsystems [30]. Additional subsystem constraints can alleviate the problem in certain limits but not universally [31][32][33]. Further, the description of open-shell systems is hardly standardised.…”
Section: Introductionmentioning
confidence: 95%